Implanting false autobiographical memories for repeated events. Issue 10 (26th November 2021) - Calado, Bruna; Luke, Timothy J.; Connolly, Deborah A.; Landström, Sara; Otgaar, Henry
ABSTRACT: Research to date has exclusively focused on the implantation of false memories for single events. The current experiment is the first proof of concept that false memories can be implanted for repeated autobiographical experiences using an adapted false memory implantation paradigm. We predicted that false memory implantation approaches for repeated events would generate fewer false memories compared to the classic implantation method for single events. We assigned students to one of three implantation conditions in our study: Standard, Repeated, and Gradual. Participants underwent three interview sessions with a 1-week interval between sessions. In the Standard condition, we exposed participants to a single-event implantation method in all three interviews. In the Repeated condition, participants underwent a repeated-event implantation method in the three interviews. The Gradual condition also consisted of a repeated-event implantation method, however, in the first interview alone, we suggested to participants that they had experienced the false narrative once. Surprisingly, within our sample, false memories rates in the Standard condition were not higher compared to the Repeated and Gradual conditions. Although sometimes debated, our results imply that false memories for repeated events can be implanted in lab conditions, likely with the same ease as false memories for single events.